Antimicrobial Resistance in Isolates from Cattle with Bovine Respiratory Disease in Bavaria, Germany - Alexander Melchner; Sarah van de Berg; Nelly Scuda; Andrea Feuerstein; Matthias Hanczaruk; Magdalena Schumacher; Reinhard K. Straubinger; Durdica Marosevic; Julia M. Riehm (MDPI AG, 2021)
Patterns of antimicrobial resistance (AMR) regarding Pasteurella multocida (n = 345), Mannheimia haemolytica (n = 273), Truperella pyogenes (n = 119), and Bibersteinia trehalosi (n = 17) isolated from calves, cattle and dairy cows with putative bovine respiratory disease syndrome were determined. The aim of this study was to investigate temporal trends in AMR and the influence of epidemiological parameters for the geographic origin in Bavaria, Germany, between July 2015 and June 2020. Spectinomycin was the only antimicrobial agent with a significant decrease regarding not susceptible isolates within the study period (P. multocida 88.89% to 67.82%, M. haemolytica 90.24% to 68.00%). Regarding P. multocida, significant increasing rates of not susceptible isolates were found for the antimicrobials tulathromycin (5.56% to 26.44%) and tetracycline (18.52% to 57.47%). The proportions of multidrug-resistant (MDR) P. multocida isolates (n = 48) increased significantly from 3.70% to 22.90%. The proportions of MDR M. haemolytica and P. multocida isolates (n = 62) were significantly higher in fattening farms (14.92%) compared to dairy farms (3.29%) and also significantly higher on farms with more than 300 animals (19.49%) compared to farms with 100 animals or less (6.92%). The data underline the importance of the epidemiological farm characteristics, here farm type and herd size regarding the investigation of AMR.